Kontribusi Pengalaman Mengajar, Motivasi Pengembangan Diri dan Penguasaan Teknologi Informasi Terhadap Kinerja Guru SMK N 2 Pengasih - yulianto .; Supriyoko .; Sukiyanto .; Rahayu Retnaningsih (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The issue underlying this research stems from the variation in teacher performance at SMK N 2 Pengasih, which is presumed to be influenced by teaching experience, self-development motivation, and information technology mastery. This study aims to determine the contribution of these three variables to teacher performance, both partially and simultaneously. The research employs a quantitative approach with data collected through questionnaires, while data analysis was conducted using multiple linear regression and partial regression techniques through SPSS version 29. The research findings show that: (1) teaching experience has a positive and significant contribution to teacher performance with an effective contribution of 12.94% and a relative contribution of 17%; (2) self-development motivation contributes positively and significantly with an effective contribution of 38.99% and a relative contribution of 52%; (3) information technology mastery contributes positively and significantly with an effective contribution of 23.44% and a relative contribution of 31%; and (4) all three variables simultaneously contribute positively and significantly to teacher performance with a total effective contribution of 75.36%. These results indicate that teaching experience, self-development motivation, and IT mastery are essential factors in improving teacher performance at SMK N 2 Pengasih.